(untitled) (Environment & Health, 2022)
Objective: We assessed the impact of the detergents, based on anionic surfactants, for the care of the children’s tableware on the indicators of the immune system of the experimental animals. Materials and methods: The effect of aqueous solutions of Alionka, Karapuz, Ushastyi Nian, Frosch Baby detergents on the indicators of the immune system was performed in the experiment with guinea pigs during 21 days. We determined the number of T- and B-lymphocytes, the number of neutrophilic granulocytes and active phagocytes; studied the reaction of the precipitation of circulating immune complexes with a solution of polyethylene glycol 6000. We used the methods of statistical processing of the results of medico-biological research. Results: The obtained results showed that the epicutaneous impact of all studied detergents for the care of children’s tableware could cause the immunomodulatory effects in the organism of guinea pigs. Changes in the largest number of the indicators of the immune system, which affected all links, were observed when exposed to Ushastyi Nian detergent. The least pronounced changes of the immunity were observed when exposed to the Frosch Baby detergent and they concerned only the indices of nonspecific resistance of the organism. The revealed inhibition of the functional activity of neutrophilic granulocytes, which was observed in animals of all experimental groups, may indicate a decrease in the protective functions of the organism of guinea pigs.